2019
DOI: 10.1097/gox.0000000000002513
|View full text |Cite
|
Sign up to set email alerts
|

Lymphedema Liposuction with Immediate Limb Contouring

Abstract: Background: Liposuction is the treatment of choice for solid predominant extremity lymphedema. The classic lymphedema liposuction technique does not remove skin excess created following bulk removal. The skin excess is presumed to resolve with spontaneous skin contracture. We investigated the technique of simultaneously performing liposuction with immediate skin excision in patients with solid predominant lymphedema and compared the outcome with that from the classic technique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Proponents of liposuction demonstrate good volume reduction and no recurrence after 5 years (Hoffner et al, 2018a). The risks of liposuction include blood loss, hematoma, contour irregularity, and skin necrosis (Chen et al, 2019). These patients need to be on lifelong compression garments.…”
Section: Management Of Lymphedema By Multi-modalities Treatmentmentioning
confidence: 99%
“…Proponents of liposuction demonstrate good volume reduction and no recurrence after 5 years (Hoffner et al, 2018a). The risks of liposuction include blood loss, hematoma, contour irregularity, and skin necrosis (Chen et al, 2019). These patients need to be on lifelong compression garments.…”
Section: Management Of Lymphedema By Multi-modalities Treatmentmentioning
confidence: 99%
“…Brorson reported that liposuction combined with postoperative controlled compression therapy (CCT) is effective for the treatment of limb lymphedema [9]. Chen et al and Chollet et al found that in liposuction without concurrent skin excision, the skin often does not sufficiently retract and can lead to wound healing complications [10,11]. However, the research results of Qi showed that limb volume reduction was noted in all cases immediately after the operation, but this state of volume reduction remained at 3 to 12 months with a mean of 6.01 months, when low-stretch bandages or compression stockings were applied.…”
Section: Introductionmentioning
confidence: 99%
“…Seven studies reporting surgical complications of SAL were documented (see Supplementary Table S3 [available in the online version], which displays an overview of the included studies). 6 56 57 58 59 A summary of the reported complications is exhibited in Table 4 . The most common complications reported were significant blood loss ( n = 30, 30.30%), transient paresthesia of the limb ( n = 32, 32.32%), contour irregularities ( n = 13, 13.13%), skin necrosis ( n = 6, 6.6%), and hematoma or seroma formation ( n = 8, 8.8%).…”
Section: Resultsmentioning
confidence: 99%